2023
DOI: 10.1007/s11255-023-03494-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape seed-derived proanthocyanidin B2 pretreatment on oxidative stress, endoplasmic reticulum stress and apoptosis of renal tubular epithelial cells in renal ischemia–reperfusion injury model of mice

Abstract: Purpose To investigate the effect of grape seed-derived proanthocyanidin B2 (GSPB2) pretreatment on acute renal ischemia–reperfusion injury model of mice. Methods 50 mice were divided into 5 groups: Sham group: mice were treated with right nephrectomy. GSPB2 group: GSPB2 was injected intraperitoneally 45 min before right nephrectomy. IRI group: right kidney was resected and the left renal arteriovenous vessel was blocked for 45 min. GSPB2 + IRI group: GSPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Thus, to clarify the therapeutic mechanism of PCs, we applied different-concentration PCs to interfere with the HSP-like cell model basing on the determination of drug safe concentrations and the establishment of cell model. Our outcomes exhibited that PCs greatly lowered the expressions of IgA, IL-4, IL-8, IL-17, TNF-α, NO, MDA and ROS, while markedly enhanced those of SOD, CAT and GSH, which was similar to the results from Wang and Chen, et al; 47 , 48 , 51–53 they discovered that PCs powerfully facilitated the decrease of inflammatory factors and oxidative substance, and the increase of antioxidants. Based on our experimental results, there does not appear to be a significant difference between the PCs groups at different concentrations when compared to the model group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, to clarify the therapeutic mechanism of PCs, we applied different-concentration PCs to interfere with the HSP-like cell model basing on the determination of drug safe concentrations and the establishment of cell model. Our outcomes exhibited that PCs greatly lowered the expressions of IgA, IL-4, IL-8, IL-17, TNF-α, NO, MDA and ROS, while markedly enhanced those of SOD, CAT and GSH, which was similar to the results from Wang and Chen, et al; 47 , 48 , 51–53 they discovered that PCs powerfully facilitated the decrease of inflammatory factors and oxidative substance, and the increase of antioxidants. Based on our experimental results, there does not appear to be a significant difference between the PCs groups at different concentrations when compared to the model group.…”
Section: Discussionsupporting
confidence: 89%
“…A serial of studies has shown that PCs actively exert in many diseases through inhibiting inflammatory factors production and arresting OS damage. [46][47][48][49] More importantly, our previous experiment tentatively uncovered that PCs could effectively alleviate cutaneous and renal injuries in HSP-like rats probably via suppression of inflammatory responses and OS insults, 50 but the exact mechanism of PCs against HSP still kept unclear. Thus, to clarify the therapeutic mechanism of PCs, we applied different-concentration PCs to interfere with the HSP-like cell model basing on the determination of drug safe concentrations and the establishment of cell model.…”
Section: Discussionmentioning
confidence: 98%